Impact of biochar and compost amendment on soil quality, growth and yield of a replanted apple orchard in a 4-year field study - Khorram, Mahdi Safaei; Zhang, Gan; Fatemi, Akram; Kiefer, Rudolf; Maddah, Kamalodin; Baqar, Mujtaba; Zakaria, Mohamad Pauzi; Li, Gang (Wiley, 2018)
BACKGROUND: Numerous studies have addressed the positive effects of organic amendments on soil and plant productivity under short-term field studies. However, to date, few studies have been conducted on the effects of organic amendment on the orchards where high nutrient bioavailability is required. This study deals with the effects of biochar and compost on soil quality, growth and yield of a replanted apple orchard in the northeast of Iran. RESULTS: Biochar+compost application resulted in 37% and 300% higher soil total organic carbon and available phosphorus content, respectively, during the first 3 years of experimentation compared to control. Similarly, trunk diameter and shoot number of apple trees increased 23–26% by the end of the first year. Nevertheless, there were no significant changes in fruitfulness, fruit weight or starch pattern index as productivity indices. CONCLUSION: Biochar and compost were beneficial in improving soil quality, mainly by increasing soil nutrient content and decreasing soil bulk density, and in increasing plant growth at early growth stages of apple orchards. However, they failed to enhance overall yield and fruit quality, most likely due to their limited ability to suppress apple replant disease. © 2018 Society of Chemical Industry. © 2018 Society of Chemical Industry